PENGEMBANGAN BUKU PENGAYAAN APRESIASI SASTRA BERHURUF BRAILLE INDONESIA DENGAN MEDIA REGLET BAGI SISWA TUNANETRA DI SEKOLAH INKLUSI KOTA SURAKARTA - Wati Istanti (Indonesian Language Education and Literature, 2016)
Objectives to be achieved in this study were (1) Finding the problems and needs of blind students, planning, and prototype book enriching appreciation of literature in Braille that can be developed in school inclusion. (2) Develop prototype (draft) enrichment of literary appreciation books in Braille for blind students in school inclusion. (3) Test the effectiveness of the application of the enrichment of literary appreciation books of the validator in Braille for blind students in school inclusion. The method in this study research design development. The subjects were blind students who will use the product of the enrichment books and Indonesian language and literature teacher who will conduct an assessment of the indicators of achievement of the basic competencies of students with visual impairment. Plan activities that have been carried out in this research is the development of book design enrichment phases: (1) a preliminary study; (2) the development stage; (3) the testing stage book; (4) dissemination of the results of the final product, namely enrichment of literary appreciation books in Braille. The final product in the form of books enrichment appreciation of literature in Braille can be used by blind students in inclusive classrooms.